Investigating the Digestive Characteristics of Lipid Emulsions with Varying ω-3/ω-6 Ratios Using in Vitro Simulated Digestion Models - Qiyue YANG; Yizhuo FAN; Yitong MO; Liyan ZHANG; Yehui ZHANG; Yousheng ZHANG; Wenjuan JIAO (Shipin gongye ke-ji)
To investigate the effects of ω-3 and ω-6 long-chain polyunsaturated fatty acids (LC PUFAs) ratios on lipid digestion properties. Using an in vitro simulated digestion model, oil-in-water (O/W) emulsions with controlled ω-3/ω-6 ratios (0, 0.62, 1.41, 9.31) were prepared to evaluate hydrolysis kinetics and bioaccessibility. Changes in particle size, ζ-potential, microstructure, and fatty acid release during the small intestinal phase of digestion were systematically examined in this study. The results showed that emulsions with varying ω-3/ω-6 ratios exhibited similar trends during digestion, distinct differences in their digestive properties were also observed. The sunflower oil emulsion (ω-3/ω-6 ratio, 0) displayed a significantly larger initial particle size compared to the other three formulations (P<0.05). This disparity was further amplified after simulated oral and gastric digestion phases, where flocculation occurred in the sunflower oil emulsion, leading to a marked increase in particle size (P<0.05). Structural destabilization was induced by gastric digestion in all four oil-in-water emulsions, with minimal electronegativity demonstrated through ζ-potential measurements during digestion. The aggregation propensity of lipid droplets and mean particle diameter exhibited an inverse correlation with increasing ω-3/ω-6 polyunsaturated fatty acid (PUFA) ratios. Systematic reduction in free fatty acid (FFA) liberation efficiency was recorded during intestinal phase simulations, proportional to elevated ω-3 content, with the descending order of sunflower seed oil (117%), mixed oil A (108%), mixed oil B (99%), and fish oil (78%) documented. The ω-3/ω-6 PUFA compositional profile was established as a critical determinant of emulsion digestibility, with superior lipolytic susceptibility demonstrated by ω-6-enriched systems.